2000
DOI: 10.1111/j.0006-341x.2000.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Nonlinear Models for Pharmacokinetic Data

Abstract: Phase I trials to study the pharmacokinetic properties of a new drug generally involve a restricted number of healthy volunteers. Because of the nature of the group involved in such studies, the appropriate distributional assumptions are not always obvious. These model assumptions include the actual distribution but also the ways in which the dispersion of responses is allowed to vary over time and the fact that small concentrations of a substance are not easily detectable and hence are left censored. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Lindsey et al [17,18] have recently pointed out that the log-normal assumption is not necessarily appropriate and other skewed distributions such as Weibull and gamma distributions may be more appropriate. The proposed approach is easily applicable to the cases where other skewed distributions are assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Lindsey et al [17,18] have recently pointed out that the log-normal assumption is not necessarily appropriate and other skewed distributions such as Weibull and gamma distributions may be more appropriate. The proposed approach is easily applicable to the cases where other skewed distributions are assumed.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, with constant coefficient of variation, is log y(t ij ) = log µ(t ij ) + (t ij ) with (t ij ) ∼ iid N(0, σ 2 ). Lindsey et al (2000) have suggested combining a compartmental model mean with a gamma error model.…”
Section: Compartmental Modelsmentioning
confidence: 99%
“…While generalized nonlinear models were not practical due to the lack of available computer software in the past, several computational options now exist to handle the requirements of generalized nonlinear models [see for example PROC NLMIXED in the SAS software package (SAS, 1999), or the GNLM module for the R statistical package (Lindsey, et al 2000]. Typically, these software solutions can estimate parameter values, as well as specified functions of the parameters.…”
Section: Generalized Nonlinear Models Analysismentioning
confidence: 99%